Sentiment Analysis of Movie Review using Machine Learning Techniques - Uma Ramya, V; Thirupathi Rao, K (International Journal of Engineering and Technology, 2018)
Today's online world was fully filled up with blogs, views, comments, posts through various websites and social-surfs. People were habituated with posting every incident into blogs, messed with comments like text and emotions, which are a mixed bag of sad, happy, worry, cry etc. Analysing such data was called as Sentimental Analysis. To analysis, these unordered data we use new emerged technology algorithms. Machine learning a transpire technology which is engaged with almost all the fields, where its algorithms are more powerful that give with better faultless results. In this paper, we are analyzing tweets based on movie reviews using the Multinomial Logistic Regression, NaÃ¯ve Bayes, and SVM algorithms to compare score value to show the best text analysis algorithm.Â